2017
DOI: 10.1080/15384101.2017.1417709
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of RelA/p65 and ACTN4 induces apoptosis in non-small lung carcinoma cells

Abstract: Alpha-actinin 4 (ACTN4) is an actin-binding protein of the spectrin superfamily. ACTN4 is found both in the cytoplasm and nucleus of eukaryotic cells. The main function of cytoplasmic ACTN4 is stabilization of actin filaments and their binding to focal contacts. Nuclear ACTN4 takes part in the regulation of gene expression following by activation of certain transcription factors, but the mechanisms of regulation are not completely understood. Our previous studies have demonstrated the interaction of ACTN4 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Studies have shown that aberrantly activated p65 (RelA) contributes to tumor development and progression [19,20]. In addition, the existence of co-immunoprecipitation between p65 and ACTN4 in non-small lung carcinoma cells has been reported [21]. Our study will further verify whether ACTN4 affects the progression of OS through the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Studies have shown that aberrantly activated p65 (RelA) contributes to tumor development and progression [19,20]. In addition, the existence of co-immunoprecipitation between p65 and ACTN4 in non-small lung carcinoma cells has been reported [21]. Our study will further verify whether ACTN4 affects the progression of OS through the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 54%
“…The activation of the NF-κB subunit P65 promotes the development of urothelial cancer and other tumors [28]. However, some researchers have found that P65 inhibits the proliferation of the lung cancer cell line H1299, and that overexpression of ACTN4 enhances this inhibitory effect [21]. Obviously, these two conclusions are in conflict with each other.…”
Section: Discussionmentioning
confidence: 99%
“…RELA, also known as p65, is one of the most common NF-kB subunits, and is involved in the classical NF-kB pathway (39). Previous research has demonstrated that RELA interacts with Alpha-actinin 4 (ACTN4) to induce proliferation and apoptosis in NSCLC cells (40). Furthermore, the nuclear overexpression of RELA was found to be significantly associated with a poor prognosis in patients with diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since ACTN4 resides in both the cytoplasm and the nucleus of eukaryotic cells, it has dual roles; the cytoplasmic and nuclear functions [68]. The former mainly involves actin filament organization as described above, while the latter takes part in the regulation of gene expression by the activation of various transcription factors, including nuclear factor-κB (NF-κB).…”
Section: Discussionmentioning
confidence: 99%
“…The former mainly involves actin filament organization as described above, while the latter takes part in the regulation of gene expression by the activation of various transcription factors, including nuclear factor-κB (NF-κB). The transcriptional regulatory function is independent of the cytoskeletal functions associated with cytoplasmic actin binding [53,[68][69][70]. Nuclear factor-κB (NF-κB) is a family of transcription factors that regulate immune responses, cell proliferation, apoptosis, and differentiation, through controlling the synthesis of target genes encoding pro-inflammatory cytokines, chemokines, and adhesion molecules [71,72].…”
Section: Discussionmentioning
confidence: 99%